Psychometric qualities of a core set to ascertain the functional profile of portuguese elderly citizens - Goes, Margarida (2020)
Objectives: This paper describes the psychometric qualities of a core set composed initially of 31 codes and extracted from International Classification of Functioning, Disability and Health, to ascertain the Functional Profile of Portuguese Elderly Citizens, residing in their own home or at a family or friends’ home. Methods: Cross-sectional, descriptive study, with a final sample totaled 351 elderlies. Data collected by health professionals in the participants’ houses, using the Elderly Nursing Core Set questionnaire. Results: The recommendation of the construct to the EFA was “excellent”. Regarding reliability, the construct revealed factorial reliability. In terms of validity, the construct presented factorial validity and convergent validity, although failing regarding discriminant validity. Discussion: Comparing psychometric qualities between the original Elderly Nursing Core Set previously applied to institutionalized citizens in relation to the one presented in this paper (citizens residing in their own home or at a family or friends’ home), lead to five latent factors and differences between functional profiles. More than half of the citizens are married and almost half of the sample never went to school, thus revealing an important aspect characterizing a lower literacy level of the citizens involved in this research. Conclusions: The work based on Core Sets extracted from the International Classification of Functioning, Disability and Health, delineated to assess the nursing care needs and/or the outcomes of nursing interventions of citizens aged 65 years old or older, will be an ongoing process that will lead to the promotion of an Healthy Ageing and functional ability, as stated by World Health Organization.